Work-Life Balance Among Gen Z and Millennials: HR Strategies Involving Leave Policies, Flexible Working Hours, and Welfare Benefits - Milawati Milawati; Hanafi Siregar; Mira Yona; Muhammad Farhan Nasution; Siti Khairani (Journal of Economics and Management Scienties, 2026)
Work-life balance has become a critical priority for young employees, particularly Millennials and Generation Z. This study presents a systematic literature review examining Human Resource (HR) strategies focused on leave policies, flexible working hours, and welfare benefits to support work-life balance among young workers. Following the PRISMA guidelines, the review synthesizes recent empirical and conceptual studies published between 2019 and 2025. The findings indicate that integrated implementation of flexible leave arrangements (including mental health days), hybrid and flextime schedules, and comprehensive wellness benefits significantly reduces burnout, enhances job satisfaction, improves retention, and increases productivity. However, the effectiveness of flexible working arrangements depends on complementary supports such as adequate allowances and clear boundary-setting mechanisms. The discussion further reveals that these three HR policies create synergistic effects when implemented holistically, while isolated or poorly supported practices may inadvertently heighten work-life conflict rather than alleviate it. Moreover, the review underscores important contextual nuances in emerging economies like Indonesia, where infrastructural limitations and organizational culture significantly influence policy outcomes. This review provides actionable insights for HR practitioners in Indonesia to design more adaptive and generation-sensitive policies that align with post-pandemic work realities and the evolving expectations of the younger workforce.